Membrane channel gene expression in human costal and articular chondrocytes. (2nd April 2016) - Asmar, A.; Barrett-Jolley, R.; Werner, A.; Kelly, R.; Stacey, M.
ABSTRACT: Chondrocytes are the uniquely resident cells found in all types of cartilage and key to their function is the ability to respond to mechanical loads with changes of metabolic activity. This mechanotransduction property is, in part, mediated through the activity of a range of expressed transmembrane channels; ion channels, gap junction proteins, and porins. Appropriate expression of ion channels has been shown essential for production of extracellular matrix and differential expression of transmembrane channels is correlated to musculoskeletal diseases such as osteoarthritis and Albers-Schönberg. In this study we analyzed the consistency of gene expression between channelomes of chondrocytes from human articular and costal (teenage and fetal origin) cartilages. Notably, we found 14 ion channel genes commonly expressed between articular and both types of costal cartilage chondrocytes. There were several other ion channel genes expressed only in articular (6 genes) or costal chondrocytes (5 genes). Significant differences in expression of BEST1 and KCNJ2 (Kir2.1) were observed between fetal and teenage costal cartilage. Interestingly, the large Ca 2+ activated potassium channel (BKα, or KCNMA1 ) was very highly expressed in all chondrocytes examined. Expression of the gap junction genes for Panx1, GJA1 (Cx43) and GJC1 (Cx45) was also observed in chondrocytes from all cartilage samples. Together, this data highlights similarities between chondrocyte membrane channel gene expressions in cells derived from different anatomical sites, and may imply that common electrophysiological signaling pathways underlie cellular control. The high expression of a range of mechanically and metabolically sensitive membrane channels suggest that chondrocyte mechanotransduction may be more complex than previously thought.